The Order of Things: An Archaeology of What? - Descombes, Vincent (History and theory, 2016)
Foucault's Les mots et les choses has been translated as The Order of Things. The title of the book, both in French and in English, would remain enigmatic without the subtitle: An Archaeology of the Human Sciences. But which disciplines are the human sciences to be accounted for by the archaeologist? To this question, there seem to be three possible answers. According to Foucault, such sciences as biology, political economy, and linguistics are indeed scientific disciplines that study human beings, but they are not human sciences. On the other hand, psychology and sociology do count as human sciences, although they are not really genuine sciences. As to structural disciplines (Lacanian psychoanalysis, Lévi-Straussian anthropology, structural linguistics), Foucault does not see them as successful human sciences, since he calls them “counter-human sciences.” In other words, the situation of the human sciences seems to be messy from the point of view of a philosopher defending the possibility of radical reflection against psychologism and more generally anthropologism. Foucault rejects Merleau-Ponty's claim to have found a way out of anthropologism through the so-called phenomenological reduction. One can read Foucault's archaeology of the human sciences as an attempt to offer an alternative way for radical thinking. His archaeology turns out to be an archaeology of ourselves insofar as it applies to archaeologists themselves, whatever knowledge they have gained of their object, the discontinuous “systems of thought” succeeding one another in history. The success of such an archaeology of ourselves will rest on the interpretation of what Foucault has rightly called the “return of language” at the center of our intellectual concerns.